Users ’ attitude towards telecommunication operators: a Study on Grameenphone and Banglalink - Ahmed, S. M. Sohel (Archives of Business Research, 2018)
Attitude is the amount of affect or feelings for or against stimulus. This study adopts with descriptive in nature. Main objective of the study is to find out users’ attitude towards telecommunication operators. Fishbeins multi-attribute model was used to measure the attitude of users of Grameenphone and Banglalink.64 salient beliefs were identified but respondents are awarded about eighteen salient beliefs. Those are network facility, SMS services, 3g services, internet modem, sports news, health line, face book services, call block, F& F services, Balance transfer, conference call, emergency balance, ring tone, internet services, promotional offer, welcome tune, availability of services and SMS alert. The users of Grameenphone has greater positive attitude than the users of Banglalink.